El papel de Suecia en la guerra civil española (1936-1939) - Fernando Camacho Padilla; Ana de la Asunción Criado (Les Cahiers de Framespa)
The coup d'etat of general Franco of the 17 - 18 of July 1936 had a stong political and social impact in Sweden. In spite of the neutrality of the Swedish government in the Spanish Civil War, part of the society organized quickly in defense of the Second Republic while the businnesmen and companies suported the rebellious troops. The first group, which was more numerous, founded solidarity committees all over the country in order to mobilize public opinion against the crimes committed by the Nationalists, and to inform of the involvement of Italy and Germany in the conflict. Their members organized fundraising campaigns with the purpose to help Republican victims. In total, around 550 Swedish citizens decided to fight with the International Brigades to contain the pro-Franco troops, a significant number of people for a country with a population of only 6.2 million inhabitants. In order to measure and evaluate the role of Sweeden during the Spanish Civil war, this article analyzes, in a global way, the attitude of the government and the political parties in the opposition, the mass media, the main characteristics of the solidarity movement, and the protagonism of the Swedish volunteers who were in the front. The investigation is based mainly on the existing bibliography in Swedish and some primary sources.